Influence of Cooling Time and Diluents on the Freezability of Prochilodus brevis semen - Nascimento, Renata Vieira do; Leite-Castro, Liliane Veras; Montenegro, Assis Rubens; Oliveira-Araújo, Mayara Setúbal; Lopes, Júlia Trugilio; Almeida-Monteiro, Priscila Silva de; Ferreira, Yasmin Maia; Salmito-Vanderley, Carminda Sandra Brito (Acta Scientiae Veterinariae, 2017)
Background: Prochilodus brevis is a rheophilic fish of economic and ecological importance. However, anthropic action has made its population vulnerable. Thus, the development of reproductive biotechnologies, such as seminal conservation, is necessary to subsidize their fish farming. However, seminal collections are often performed in places with few laboratory resources, demanding studies to determine the maximum time for which sperm can be cooled, as well as its process until frozen. Thus, the present study aimed to evaluate the influence of cooling time and the presence of dilution solutions on cryopreservation of P. brevis semen. Material, Methods & Results: After seminal collection, nine pools were formed and analyzed for seminal pH, concentration, membrane integrity, morphology and spermatic kinetics - motility, curvilinear velocity (VCL), average path velocity (VAP) and straight line velocity (VSL). After the analysis of the pools in natura (control 1), they were processed as follows: 1)- immediate freezing (control 2); 2)- cooling: undiluted, diluted in coconut water powder (ACP-104) or diluted in 5% glucose, followed by cooling at different times (6, 12, 24 or 48 h); 3)- Post-refrigeration freezing: the pools were diluted in their respective diluents and 10% dimethyl sulfoxide. After 15 days, the samples were thawed and analyzed for the aforementioned parameters. For the cooled and post-thawed semen, a completely randomized design with 2 (diluent × cooling time) and 3 (storage form × cooling time and storage form × diluent) factors, respectively, was utilized. ANOVA and Dunnett tests were applied to compare the means. In case of seminal cooling, there was no difference (P > 0.05) in sperm motility between control 1 and the undiluted and diluted treatments in ACP-104 for up to 24 h. After 48 h, only the VCL of the sample diluted in ACP-104 was similar (P > 0.05) to that of control 1. When comparing forms of storage (undiluted, diluted in ACP-104 or diluted in glucose) and cooling times, the undiluted samples and the samples diluted in ACP-104 were better (P < 0.05) for all the kinetics parameters analyzed, than those diluted in glucose after 24 h. After 48 h, the cooled semen diluted in ACP-104 presented greater (P < 0.05) motility than the other treated semen samples. The samples diluted in glucose for 48 h presented lower spermatic velocity (P < 0.05) than those subjected to other treatments. Regardless of the diluent used, the post-thawed semen and the cooled semen diluted for 6 h, presented higher sperm kinetic values (P < 0.05) than those of control 2 and other treated samples. Overall, the samples diluted in ACP-104 showed satisfactory results when cooled for up to 48 h or cooled for up to 6 h and frozen. Discussion: This is the first study that froze semen from P. brevis after cooling. Although glucose is a commonly used diluent during seminal freezing and has good post-thawing stability for this species, it is not recommended for cooling before seminal freezing, as prolonged exposure of spermatozoa to glucose may cause osmotic stress to sperm cells. Conversely, good results with ACP-104 might be because of its rich composition, mainly the presence of indole-3-acetic acid (IAA), an auxin with proven potential for seminal conservation of other species. Therefore, for fertilization trials, it is recommended to use ACP-104 as diluent for seminal cooling of P. brevis for up to 48 h or semen that has been frozen after cooling in ACP-104 for a maximum of 6 h.